NUTRITIONAL CHARACTERIZATION AND REGIONAL VARIABILITY OF CORN GRAINS FOR MONOGASTRIC ANIMAL FEEDING IN WESTERN ROMANIA - Hotea, Ionela (Food and Feed Research, 2025)
Abstract: The objective of this study was to evaluate the nutritional quality and variability of corn grains used in the diet of monogastric animals, with a focus on samples collected from three counties in western Romania: Timiș, Arad, and Caraș-Severin. The analyzed corn kernels originated from the local hybrid Fundulea 350 were collected from regional grain collection centers after harvest and were analyzed to determine their chemical composition, amino acid profiles, and energetic parameters relevant to swine and poultry nutrition. Near-infrared reflectance spectroscopy (NIR) was employed to assess dry matter, crude protein, ether extract, crude fiber, ash, starch, and the concentrations of essential and non-essential amino acids. The results revealed significant interregional differences. Dry matter content ranged from 85.40% (Caraș-Severin) to 90.50% (Timiș), indicating generally good preservation conditions. Crude protein concentrations exhibited marked variability between regions, with highest values recorded in Timiș (up to 10.72%) and lowest in Caraș-Severin (minimum 6.67%). Lysine levels varied between 0.213% and 0.312%, while methionine ranged from 0.167% to 0.219%. Total starch content was consistently high (61.9–66.6%), supporting substantial energy contributions. Metabolizable energy for growing pigs (ME_GP) ranged from 13.61 MJ/kg in Caraș-Severin samples to 14.62 MJ/kg in Timiș samples. All samples contained a high proportion of phytic phosphorus (74–76%), underscoring the need for phytase supplementation to improve phosphorus bioavailability. The variability observed among regions emphasizes the importance of locally specific nutrient analysis to inform precise diet formulation and optimize performance in monogastric animal production. These findings highlight the critical importance of regional nutrient profiling to support precision diet formulation in swine and poultry production. Targeted selection and strategic blending of corn batches can improve protein supply, amino acid adequacy, and feed energy density, ultimately enhancing production efficiency and sustainability in monogastric systems.
Keywords: corn, nutrition, swine, poultry, NIR